Characterization of an autonomously replicating region from the Streptomyces lividans chromosome. - Zakrzewska-Czerwińska, J (1992)
The chromosomal replication origin of the plasmidless derivative (TK21) from Streptomyces lividans 66 has been cloned as an autonomously replicating minichromosome (pSOR1) by using the thiostrepton resistance gene as a selectable marker. pSOR1 could be recovered as a closed circular plasmid which shows high segregational instability. pSOR1 was shown to replicate in Streptomyces coelicolor A3(2) and in S. lividans 66 and hybridized with DNA from several different Streptomyces strains. Physical mapping revealed that oriC is located on a 330-kb AseI fragment of the S. coelicolor A3(2) chromosome. DNA sequence analyses showed that the cloned chromosomal oriC region contains numerous DnaA boxes which are arranged in two clusters. The preferred sequence identified in the oriC region of Escherichia coli and several other bacteria is TTATCCACA. In contrast, in S. lividans, which has a high GC content, the preferred sequence for DnaA boxes appears to be TTGTCCACA.